Enhancing PSMA-uptake with androgen deprivation therapy – a new way to detect prostate cancer metastases? - Leitsmann, Conrad (Int Braz J Urol, 2019)
PURPOSE: (68)Ga-PSMA PET/CT imaging is a promising modality for the staging of recurrent prostate cancer (PCa). Current evidence suggests limited diagnostic value of the (68)Ga-PSMA PET/CT in PSA-levels ≤0.3ng/mL. Experimental data have demonstrated an increase in PSMA-expression in PCa metastases by androgen deprivation in vitro. The aim of the current study was to investigate a possible enhancing effect of PSMA with low-dose androgen deprivation in patients with BCR and low PSA-levels. MATERIALS AND METHODS: Five patients with PCa and BCR, following radical prostatectomy, underwent (68)Ga-PSMA PET/CT. A consecutive (68)Ga-PSMA PET/CT was performed 6 to 11 days after injection of 80mg of Degarelix (Firmagon(®)). We recorded PSA and testosterone serum-levels and changes of PSMA-uptake in (68)Ga-PSMA PET/CT images. Results: Median PSA prior (68)Ga-PSMA PET/CT was 0.27ng/mL. All patients had a decrease in testosterone serum levels from median 2.95μg/l to 0.16μg/l following Degarelix injection. We observed an increase in the standardized uptake value (SUV) in PSMA-positive lymphogenous and osseous lesions in two patients following androgen deprivation. In another two patients, no PSMA positive signals were detected in either the first or the second scan. CONCLUSION: Our preliminary results of this feasibility assessment indicate a possible enhancing effect of PSMA-imaging induced by low-dose ADT. Despite several limitations and the small number of patients, this could be a new approach to improve staging by (68)Ga-PSMA PET/CT in PCa patients with BCR after primary therapy. Further prospective studies with larger number of patients are needed to validate our findings.